Klinična biokemija pri obravnavi ledvičnih zapletov sladkorne bolezni - Černe, Darko (Farmacevtski vestnik, 2005)
Here we describe the importance of medical biochemistry in diagnosis and monitoring of renal complications of diabetes mellitus, such as diabetic nephropathy, renal artery atherosclerosis, pielonephritis and papillary necrosis. Microalbuminuria (early increase of albumin concentration in urine) is nowadays the strongest and the most frequently used prognostic marker of advanced diabetic nephropathy and diagnostic indicator of an early disease, therefore, measurement of albumin concentration in urine of diabetic patients should be regularly measured according to the recommended guidelines. Von Willebrand factor activity in plasma and renal functional reserve, nowadays used in research only, may become in future a part of a routine laboratory diagnostics of diabetic nephropathy. In renal artery atherosclerosis laboratory diagnostics has only minor importance and is limited to analysis ofĆconventionalĆ parameters for atherosclerotic risk stratification (lipids, lipoproteins, C-reactive protein, homocysteine). In diagnosis and treatment ofpielonephritis and papillary necrosis basic urinalysis has important role and should be regularly performed. Our overview may be of help when choosing appropriate laboratory assays for diagnosis and monitoring of renal complications of diabetes mellitus.
Keywords: diabetes mellitus; klinična biokemija; ledvične bolezni; sladkorna bolezen